(untitled) (GEON Journal (Management, Organizations and Business), 2016)
It is vital to study the work environment, as an indicator measuring satisfaction, the performance of employees in their work environment, and identify areas of opportunity in business. For this purpose an instrument was applied and measuring the perception of the working climate in service sector companies in the city of Puebla, determining a sample of 311 organizations with an average of 0-10 employees, the questionnaire is divided into eight dimensions, as a) Staff satisfaction in their work, b) The opinion held by workers to their superiors, c) Fellowship at work d) Opinion on the job, e) gender equity, f) Time in Company g) Salary Compensation, h) Comfort and ergonomics. From the results the dimension that has a better assessment is d) Opinion on the job, and the lowest f) remained the worker in the company reflecting mobility of workers seeking opportunities.